International and Language Education for a Global Future - David S. Wiley, Robert S. Glew (Michigan State University Press, 2012)
In this introduction, we review some of the history of the Title VI programs, including the spirit of the moment of their founding during the Cold War and the twentieth-century context for their directions. Various essays in this volume address the changing character of the programs and new directions to consider in light of new needs and the maturing of the programs. Year after year, these centers, usually providing a 4:1 (sometimes 10:1) match of university to federal funds, have built the foundation of America’s intellectual effort to comprehend the new global world of the twentieth and twenty-first centuries. They have conducted research on internationalizing the American university, built the corpus of language learning materials for use in college and government, improved language learning pedagogies, erected the most distinguished U.S. library holdings on foreign regions, supported indepth research abroad in virtually every nation, and created capacity to teach 200 less commonly taught languages (LCTLs). Elaine Tarone’s chapter provides a broad overview of Title VI accomplishments in the LCTLs in the National Resource Centers (NRCs), LRCs, and Foreign Language and Area Studies (FLAS) programs, affecting a range of learners from K-12 students to PhD candidates. In addition, these centers have brought new seriousness to the service or outreach mission of their agendas, offering language and area expertise to the K-12 and college communities, state and federal governments, businesses, and the media. To cope with the globalizing world, these centers do not teach insularly about customs of isolated peoples and cultures but rather teach about societies in a globalizing Africa, Asia, Latin America, and more cast in a context of global change in economics, politics, society, and communications.